Probing Dynamic Features of Phagosome Maturation in Macrophage using Au@MnOx@SiO2 Nanoparticles as pH‐Sensitive Plasmonic Nanoprobes. Issue 9 (31st March 2021) - Shang, Jinhui; Yang, Qian; Fan, Wenjun; Chen, Yancao; Tang, Decui; Guo, Haowei; Xiong, Bin; Huang, Shuangyan; Zhang, Xiao‐Bing
Abstract: Phagosome maturation in macrophage is essential to the clearance of pathogenic materials in host defence but the dynamic features remain difficult to be measured in real time. Herein, we reported the multilayered Au@MnOx @SiO2 nanoparticle as a robust pH‐sensitive plasmonic nanosensor for monitoring the dynamic acidification features over the phagosome maturation process in macrophage under darkfield microscopy. For this multilayered nanosensor, the gold nanoparticle core plays a role of signal reporter, the MnOx shell and the outmost SiO2 act as the sensing layer and the protecting layer, respectively. After subject to the acidic buffer solution, the MnOx layer in the multilayered nanoprobe could be decomposed rapidly, resulting in a remarkable spectral shift and color change under darkfield microscopy. We demonstrated this nanosensor for the investigation of single phagosome acidification dynamics by monitoring the color changes of nanoprobes after phagocytosis over time. The nanoprobes after phagocytosized in macrophage displayed a slight color change within the first hour and then cost several minutes to change from red to green in the next stage, indicating the phagosome undergoes a slow first and then fast acidification feature as well as a slow‐to‐fast acidification translation over the phagosome maturation process. Moreover, we validated that the slow‐to‐fast acidification translation was dependent on the activation of V‐ATPase from the ATP depletion assay. We believed that this nanosensor is promising for studying the dynamic acidification features as well as disorders in phagosome maturation in phagocytic cells, which might provide valuable information for understanding the disease pathogenesis related to phagosome dysfunctions. Abstract : Robust plasmonic nanosensor : Multilayered Au@MnOx @SiO2 nanoparticles acting as a pH‐sensitive nanoprobe are reported to measure the dynamic features of phagosome acidification over the maturation process. By analyzing the time‐dependent color changes of nanoprobes after phagocytosized by macrophage, a slow acidification stage at hour time scale and a fast acidification at minute time scale as well as an ATP‐dependent slow‐to‐fast acidification translation were uncovered.